ANALISIS DENDA KETERLAMBATAN KPR SYARIAH PERSPEKTIF QAWĀʿID FIQHIYYAH - Fathayadimyati, Irfan Hakim; Al Farizi, Reza; Rohiyati; Samsudin, Agus Rojak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the application of late payment penalties in Islamic Home Financing (Kredit Pemilikan Rumah or KPR) from the perspective of Qawāʿid Fiqhiyyah (Islamic legal maxims). The research employs a qualitative approach using a library research method. Data were collected through the examination of the Fatwa of the National Sharia Council–Indonesian Council of Ulama (DSN-MUI), statutory regulations, books, and scholarly articles related to Islamic home financing, the concept of ta'zir (disciplinary sanctions), and Islamic legal maxims. The data were analyzed using content analysis to identify, classify, and interpret relevant information based on applicable fiqh principles. The findings indicate that the imposition of late payment penalties (ta'zir) is permissible in Islamic home financing, provided that the penalties are imposed only on financially capable customers who intentionally delay payment, are not recognized as bank income, and are allocated to social welfare purposes in accordance with DSN-MUI Fatwa No. 17/DSN-MUI/IX/2000. From the perspective of Qawāʿid Fiqhiyyah, the implementation of such penalties is consistent with the legal maxims al-ḍarar yuzāl (harm must be eliminated), al-umūr bi maqāṣidihā (matters are judged by their objectives), al-masyaqqah tajlib al-taysīr (hardship begets facilitation), and al-ghunmu bi al-ghurmi (gain is accompanied by liability), as they aim to uphold public welfare, justice, and a balance of rights and obligations between the contracting parties. Therefore, the implementation of late payment penalties in Islamic home financing is considered consistent with the principles of Islamic Economic Law when applied fairly, proportionately, and in accordance with Sharia principles.